2004
DOI: 10.1590/s0103-90162004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization and soil management of winter common bean crop

Abstract: The adoption of appropriate cultural management, which includes nitrogen fertilization and soil tillage system, is very important to increase the efficiency of plant in the utilization of available resource. This research work was conducted for three years aiming at evaluating the effect of sidedressing nitrogen application (0, 25, 50, 75, and 100 kg ha -1 ) on winter bean crop under different systems of soil management (conventional, minimal, and no-tillage systems). The experimental design was a randomized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
3
5
0
3
Order By: Relevance
“…These results are similar to multiple studies that have demonstrated the positive effect of N on 100 grain weight (Rapassi et al, 2003;Silva et al, 2004;Alvarez et al, 2005;Teixeira et al, 2005;Binotti et al, 2009). However, Bassan et al (2001) observed higher values in the inoculated treatments in relation to the non-inoculated ones and attributed the result to the non-existence of efficient native strains.…”
Section: Resultssupporting
confidence: 92%
“…These results are similar to multiple studies that have demonstrated the positive effect of N on 100 grain weight (Rapassi et al, 2003;Silva et al, 2004;Alvarez et al, 2005;Teixeira et al, 2005;Binotti et al, 2009). However, Bassan et al (2001) observed higher values in the inoculated treatments in relation to the non-inoculated ones and attributed the result to the non-existence of efficient native strains.…”
Section: Resultssupporting
confidence: 92%
“…In addition, topdressing N fertilization is a widespread practice to sustain high yields of common bean. The biological N fixation does not supply an adequate amount of N to bean plants (Coelho et al, 1998;Silva et al, 2004). Furthermore, several researchers have reported that N fertilization improves nutritional and yield parameters of common bean (Silva et al, 2004;Amaral et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The biological N fixation does not supply an adequate amount of N to bean plants (Coelho et al, 1998;Silva et al, 2004). Furthermore, several researchers have reported that N fertilization improves nutritional and yield parameters of common bean (Silva et al, 2004;Amaral et al, 2016). However, there is still a great lack and conflict of information related to the amount of N provided on the physiological aspects of the common bean seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Para que a cultura expresse todo o seu potencial é necessário que o nutriente seja colocado no tempo e em local adequados. Diversos autores têm demonstrado que a adubação nitrogenada promove incrementos na produtividade de grãos do feijoeiro de inverno, em sistema plantio direto, utilizando-se doses de até 85 kg ha -1 de N (SILVEIRA e DAMASCENO, 1993;CHIDI et al, 2002;BORDIN et al, 2003, SILVA et al, 2004. Há ainda resultados em que o feijoeiro responde à adubação acima de 100 kg ha -1 (BARBOSA FILHO e SILVA, 2000;STONE e MOREIRA, 2001;CARVALHO et al, 2003;SILVA et al, 2003;MEIRA et al, 2005).…”
unclassified